2019
DOI: 10.1111/tri.13505
|View full text |Cite
|
Sign up to set email alerts
|

The temporal and long‐term impact of donor body mass index on recipient outcomes after kidney transplantation – a retrospective study

Abstract: The impact of increasing body mass index (BMI) on development and progression of chronic kidney disease is established. Even implantation kidney biopsies from obese living donors demonstrate subtle histologic changes despite normal function. We hypothesized that kidneys from obese living (LD) and deceased donors (DD) would have inferior long-term allograft outcomes. In a study utilizing US transplant registry, we studied adult kidney transplant recipients from 2000 to 2014. Donors were categorized as BMI <20 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 33 publications
(40 reference statements)
0
20
1
Order By: Relevance
“…This pattern highlights the need for larger prospective studies capable of further exploring these variables. Of note, however, is the fact that in our study average BMI of the donors was 24.28 kg/m 2 and only 6 donors had a BMI >30 kg/m 2 , previously identified as a risk threshold [28]; thus, our results should be interpreted with caution.…”
Section: Discussioncontrasting
confidence: 63%
“…This pattern highlights the need for larger prospective studies capable of further exploring these variables. Of note, however, is the fact that in our study average BMI of the donors was 24.28 kg/m 2 and only 6 donors had a BMI >30 kg/m 2 , previously identified as a risk threshold [28]; thus, our results should be interpreted with caution.…”
Section: Discussioncontrasting
confidence: 63%
“…Previous studies have shown that donor obesity is associated with DGF, primary non‐function (PNF), acute rejection and inferior long‐term kidney allograft survival [4,12,13]. Naik et al .…”
Section: Introductionmentioning
confidence: 99%
“…Naik et al . [13] demonstrated that with both living and deceased kidney donors, having a BMI ≥ 35 kg/m 2 , was associated with an increased risk of long‐term allograft failure (hazard ratio 1.22; 95% CI 1.14–1.31, P < 0.01). Alhamad et al .…”
Section: Introductionmentioning
confidence: 99%
“…BMI is another important factor affecting transplantation outcomes, as donor obesity is a reported risk factor for graft failure. In contrast, smaller recipients of larger donor kidneys have been linked to better long-term outcomes (10). This difference in BMI can also reduce the possibility of graft loss for sex-mismatched recipients (11).…”
Section: Introductionmentioning
confidence: 99%